Managing the Diversity of a Continent: Balancing Africa’s Rich Heritage with Development Needs - (:unkn) unknown (My University, 2022)
Africa is endowed with diverse and rich cultural and natural heritage. From snowcapped mountains, great rivers, tropical forests and savannas, hominid sites, rock art, modern architecture and townscapes, memory of slavery and colonial heritage to cultural landscapes and sacred sites, Africa is a continent of plenty. With a long history of interaction including with the other parts of world, the continent is also rich in intangible heritage, including hundreds of languages, music, dance, traditions and rituals unique to it.With its rich natural resources including gas and oil, forest products and minerals, the changing lifestyles and global interaction including through social media the protection of some of these rich heritages, tangible and intangible and including some world heritage have become a challenge as conflicting interests occur on the landscape and within the various communities. This is more so as governments try to balance benefits of conservation and development with the two often seen as in conflict.This chapter looks at some of the rich African’s heritage, tangible and intangible, movable and immovable, their potentials as well as the challenges faced (Abungu 1994, 1998, 2004, 2005). It interrogates the notion of inherent conflicts between heritage management and development in Africa with a view towards reaching a middle ground of win-win situation. This topic is relevant to China as the country is one of the largest investors in the African continent and would obviously prefer to see developments that do not negatively impact on the cultural heritage of Africa. To the contrary, one would envisage it promoting developments that enhance existing rich cultural and natural heritage, something that at theoretical level has already been demonstrated by China sponsoring international conferences on heritage and development in Africa.
Keywords: African Research